Preparation method of YAG-nano terbium oxide composite magneto-optical transparent ceramic - TU XIUFEN (2017)
The invention discloses a preparation method of a YAG-nano terbium oxide composite magneto-optical transparent ceramic. The transparent ceramic with the magneto-optical performance is prepared from YAG powder serving as a main component and composite nano terbium oxide through the steps of material mixing, screening, vacuum degassing, tape casting, adhesive discharging, isostatic cool pressing, sintering and grinding and polishing. The ceramic is good in transparency and high in Verdet constant; nano terbium oxide is prepared through large-scale alcohol heating, the method is simple and practical, large-scale preparation can be achieved, and the prepared terbium oxide nanoparticles have the good size uniformity and the monodispersity in an alcoholic solution. 本发明公开了种YAG-纳米氧化铽复合磁光透明陶瓷的制备方法，以YAG粉体为主要成分，复合纳米氧化铽，通过混料、过筛、真空脱气、进行流延成型、排胶、冷等静压、烧结、研磨抛光，制得得到具有磁光性能的透明陶瓷，该陶瓷透明度好，费尔德常数高；该纳米氧化铽采用大规模醇热制备，该方法简单实用，可大规模制备，所制备的氧化铽纳米颗粒具有较好的尺寸均性以及醇溶液中的单分散性。